2023
DOI: 10.1186/s13195-023-01162-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into sex-specific metabolic alterations in Alzheimer’s mouse brain using multi-omics approach

Abstract: Background Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that is characterized by altered cellular metabolism in the brain. Several of these alterations have been found to be exacerbated in females, known to be disproportionately affected by AD. We aimed to unravel metabolic alterations in AD at the metabolic pathway level and evaluate whether they are sex-specific through integrative metabolomic, lipidomic, and proteomic analysis of mouse brain tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 126 publications
1
1
0
Order By: Relevance
“…Further transcriptomic analysis identified that the number of differentially expressed genes, particularly those related to glucose metabolism, was 3 times greater in female, compared with male AD, patients ( Park et al, 2023 ). Similar sex-specific differences have been reported in animal models of AD ( Guillot-Sestier et al, 2021 ; Strefeler et al, 2023 ). Impaired mitochondrial function is also a recognized change in the brains of AD patients ( Wang et al, 2020 ) and animal models of AD ( Fang et al, 2019 ; Demarest et al, 2020 ) and the evidence indicates that mitochondrial metabolism is particularly compromised in female APP/PS1 mice ( Demarest et al, 2020 ; O’Neill et al, 2022 ).…”
Section: Is There Evidence Of Sex-related Differences In Response To ...supporting
confidence: 83%
“…Further transcriptomic analysis identified that the number of differentially expressed genes, particularly those related to glucose metabolism, was 3 times greater in female, compared with male AD, patients ( Park et al, 2023 ). Similar sex-specific differences have been reported in animal models of AD ( Guillot-Sestier et al, 2021 ; Strefeler et al, 2023 ). Impaired mitochondrial function is also a recognized change in the brains of AD patients ( Wang et al, 2020 ) and animal models of AD ( Fang et al, 2019 ; Demarest et al, 2020 ) and the evidence indicates that mitochondrial metabolism is particularly compromised in female APP/PS1 mice ( Demarest et al, 2020 ; O’Neill et al, 2022 ).…”
Section: Is There Evidence Of Sex-related Differences In Response To ...supporting
confidence: 83%
“…Metabolic abnormalities have been associated with neurodegenerative diseases [ 17 ]. Alzheimer’s disease (AD) patients are accompanied by alterations in energy and lipid and amino acid metabolism [ 18 ]. Additionally, metabolites play a crucial role in cellular function, and any changes in metabolites reflect the outcome of molecular biology [ 19 ].…”
Section: Introductionmentioning
confidence: 99%